Enzyme replacement therapy with galsulfase for mucopolysaccharidosis VI: clinical facts and figures - Harmatz, Paul (The Turkish Journal of Pediatrics, 2010)
Mucopolysaccharidosis VI (MPS VI) is an inheritable, clinically heterogeneous lysosomal storage disorder that develops due to a deficiency in the arylsulfatase B (ASB) enzyme. This deficiency impairs the stepwise degradation of glycosaminoglycans (GAGs) resulting in the accumulation of partially degraded GAGs in tissues and organs throughout the body. A relatively novel therapy for MPS VI is enzyme replacement therapy (ERT) with human recombinant ASB (galsulfase). This manuscript gives an overview of all clinical trials that have evaluated the efficacy and safety of ERT with galsulfase in patients with MPS VI to date and discusses the outcome of these trials.